Tradisi Nyongkolan di Lombok perspektif hukum adat - Farohah, Mu’tiyatul (Maliki Interdisciplinary Journal, 2023)
The main purpose of making this article entitled The Role of International Law in Overcoming Society is a form of life togetherIts citizens interact for a long time so that it gives birth culture. Society is a social system that becomescontainer of various patterns of social interaction or human personal relationships as well as relationships between social groups. Communities that give birth to culture and traditions are called customary law communities. The nyongkolan tradition formed in Lombok is one of the most meaningful and preserved traditions. People who maintain traditions are aware that these traditions are born with good meaning. The nyongkolan tradition aims to strengthen friendship between two families who were previously foreigners. So this tradition is in accordance with the meaning of marriage which binds two families through the married couple. This tradition is carried out accompanied by music which has the aim of spreading information that the two brides who are paraded have married. Nyongkolan tradition is one of themtraditions that have become customary law for the people of Lombok, especially the Sasak tribe. Customary law is carried out with bonds of mutual trust so that it is compatible with the nyngkolan tradition of the people of Lombok. The tradition of nyongkolan perspective in customary law is the focus of discussion in this article. The author examines the nyongkolan tradition using the lens of customary law.